Youth Conceptualization of Resilience Strategies in Four Low- and Middle-Income Countries - Vostanis, Panos; Haffejee, Sadiyya; Yazici, Hikmet; Hussein, Sajida; Ozdemir, Munevver; Tosun, Cansu; Maltby, John (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
The concept of resilience is increasingly influential in the development of interventions and services for young people, yet there is limited knowledge of how resilience-building strategies are conceptualized by young people across different cultures, particularly in low- and middle-income countries. The aim of this study was to capture 274 young people’s voices in disadvantaged communities in Kenya, Turkey, Pakistan, and Brazil through participatory research methods. Young people defined strategies in response to 4 adversity scenarios reflecting socioecological systems (young person, family, school, and community). Template analysis, underpinned by thematic design, was used to establish three broad themes of intrapersonal (self-management, cognitive re-appraisal, agency), interpersonal (social engagement, informal supports, formal supports), and religious resources. Proposed strategies were largely similar across the sites, with some contextual differences depending on the scenario (stressor) and cultural group. The findings support an ecological systems approach to resilience, which is consistent with the development of multimodal interventions for vulnerable youth and their families in disadvantaged communities in low- and middle-income countries.